2020
DOI: 10.21037/mhealth.2019.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile health in diabetic retinopathy awareness and eye care behavior among Indigenous women

Abstract: Background: Diabetes is increasingly widespread among Indigenous people, and diabetic retinopathy (DR) is a diabetes eye complication and a common cause of vision loss among adults in Canada. Indigenous women have a high risk of diabetes which increases their risk for DR. This study explored utilizing mobile health (mHealth) via text messages to provide DR awareness and improve diabetic-eye care behavior. This study identified the changes in DR awareness and eye care behavior due to a mHealth education interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“… 66 One model described the use of mobile phones (mobile health) to carry out eye health promotion regarding diabetic retinopathy with Indigenous women in Canada. 67 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 66 One model described the use of mobile phones (mobile health) to carry out eye health promotion regarding diabetic retinopathy with Indigenous women in Canada. 67 …”
Section: Resultsmentioning
confidence: 99%
“…66 One model described the use of mobile phones (mobile health) to carry out eye health promotion regarding diabetic retinopathy with Indigenous women in Canada. 67 Lastly, eight models focused exclusively on access to trachoma control measures in the USA (n=1) 68 and Australia (n=7). [69][70][71][72][73][74][75][76][77] Trachoma requires specific, welldefined interventions which are not widely applicable to other eye conditions: SAFE (surgery for trichiasis, mass antibiotic distribution, promotion of facial hygiene and environmental change).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…mHealth apps are intended to give empowerment to its users to self-manage their problems and render social justice to get the solution when he is incapacitated by various means to reach health care. Many patients having Non-Communicable Diseases like Diabetics, Obesity, COPD are using wearable sensors, belt etc to monitor their calorie intake, exercise, partial oxygen saturation etc [17]. Though at a first look it appears, these Apps and digital tools empower patients and enhance their autonomy, when critically analysed it is not so.…”
Section: Efficiency and Preventionmentioning
confidence: 99%
“…It helps by providing autonomy, competency and his own responsibilities to follow the desired health behaviour. 5 The community can also be made aware of DR related health promotional sources available for the visually impaired population. 6 Another study conducted in an urban province of the Sultanate of Oman identified that only 24% of the schools' students population had adequate knowledge about diabetes.…”
mentioning
confidence: 99%
“…Such tools support the individuals having diabetes, or the communities at risk in prevention as well as further managements in improving their quality of life. 5 An intervention design based on the systematic approach followed by applying the different theories based on the consensus of the various stakeholders is more likely to be successful in improving the health outcomes within the affected community. 11 However, there are limited studies evaluating the impact of the various DR health educational resources on enhancing the knowledge level amongst the community.…”
mentioning
confidence: 99%